Bearing strength and failure behavior of pinned hybrid glass-flax composite laminates. (August 2018) - Fiore, V.; Calabrese, L.; Scalici, T.; Bruzzaniti, P.; Valenza, A.
Abstract: The aim of the present work is to evaluate the influence of external layers of glass woven fabric on the pin-hole strength of flax/epoxy laminates. Single lap bearing tests were carried out to evaluate the fastened joint performances depending on laminate stacking sequence. In order to better identify the mechanical behavior of the hybrid laminate, full glass and flax laminates were also compared. In particular, bearing stress and failure mechanisms were investigated at varying joint geometry. Furthermore, an experimental failure map, clustering main failure modes of pinned hybrid composite laminate, was used to better clarify the relationship between mechanical failure and geometrical parameters of joints. The experimental results showed that the presence of external layers of glass fabric in a flax/epoxy laminate positively influences the mechanical performance of mechanically fastened joints. Furthermore, in a hybrid laminate, bearing fracture mechanism occurs for a large range of joint geometries, thus supporting the joining design of flax based composite laminates. Highlights: The bearing behavior of pin-loaded hybrid glass-flax laminates was investigated. Bearing stress evolution and failure mechanisms were investigated at varying pin diameter and hole to free edge distance. The external glass layers positively influence the mechanical performances of pin-loaded flax laminates. Hybridization with glass allows to enlarge the bearing area in the failure map. E/D and W/D ratios must be higher than 2.4 and 3.1 to achieve the full laminate strength.